(untitled) (TAMADDUN NURI JURNALI, 2025)
The article is devoted to the analysis of the creative laboratory of writers of the XIX–XX centuries, a space in which ideas, plots and artistic techniques were formed that determined the development of world literature. The features of the literary work of such authors as A.S.Pushkin, F.M.Dostoevsky, L.N.Tolstoy, A.P.Chekhov, M.Proust, F Kafka and J.Joyce. Attention is paid to drafts, diaries, letters and memoirs of contemporaries as sources for studying the creative process. Special attention is paid to the influence of the historical context, philosophical and aesthetic ideas on the style and structure of the works. The purpose of the article is to show how the individual path of a writer, his inner world and method of work are reflected in his literary heritage.